Biotrade and the valuation of Amazonian Forest biodiversity in the central jungle of Peru (Aporte Santiaguino, 2025)
The objective of this study was to analyze the relationship between sustainable Biotrade and the valuation of Amazonian Forest biodiversity in Peru’s central jungle. A quantitative methodology was applied, with an applied, non-experimental, correlational, and cross-sectional design. The sample was non-probabilistic and intentional, composed of actors linked to responsible biodiversity use. A structured questionnaire with dichotomous closed questions was used, organized into thematic dimensions. The results show high levels of cultural valuation (83%) and positive perception of forest product commercialization (78%). A significant relationship between variables was found (p = 0.003). It is concluded that biotrade strengthens forest valuation by generating economic, social, and ecological benefits. It is recommended to align local policies and sustainable value chains to ensure effective conservation.
Keywords: Biotrade biodiversity; Central jungle; Environmental valuation; Sustainable development